Assessment of tourists satisfaction and perception in Markurdi Zoological garden, Benue state, Nigeria (2015)
The assessment of tourists’ satisfaction and perception in Makurdi Zoological garden, Nigeria was elucidated using two sets of structured questionnaires; in-depth interview and desk review. This paper explores the underlying reasons accounting for tourists’ tendency to repeat their visit and preferences in the garden, the category of people who patronized the zoo most and sourcing visitors’ views on what can be done to make the garden more viable. Descriptive statistics (frequencies, percentages and line graph) and the Pearson chisquare test of independent were used in data analysis. Results analyzed revealed that student groups (70%) in primary, secondary and tertiary cycle patronized the garden most. The purpose of visitation among tourists was for education (35%) and viewing of animals (33%). The most preferred wildlife species visitors came to view were lion, elephants, chimpanzee, monkeys, crocodile, and birds respectively. Tourists express dissatisfaction over diversity/welfare of fauna species in the zoo, route network, security/ protection against hazards and the abandoned areas like the picnic, museum and restaurants. They also perceived that good management, proper advertisement, good landscape (horticulture), restocking and rehabilitation of depilated or abandoned facilities will promote patronage, create satisfaction and equally step up the revenue of the garden. Age and gender has no significant effect on visitation to the zoo (α0.05) while marital status and occupation was observed to have (α0.05). The recommendation is made that government should increase its financial commitment, improve on its management strategies and renovate dilapidated and abandoned structures to make the garden attractive and viable.